2019
DOI: 10.1029/2018jg004672
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Phytoplankton Dynamics During Typhoon Season in and Near the Pearl River Estuary, South China Sea

Abstract: The effect on phytoplankton dynamics of nutrient inputs from rivers within the highly eutrophic Pearl River Estuary (PRE) in China is well understood. However, the role that typhoons play in enhancing or reducing phytoplankton blooms is less well known. The primary factors controlling phytoplankton dynamics in the PRE in June-July 2009 were determined by coupling satellite remote sensing data with field observations during two successive typhoons: Nangka and Soudelor. The results revealed that the magnitude of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…1c, d) and offshore spreading of the river plume. A stronger bloom was identified in the surface plume, widely spreading from the mouth of the Lingdingyang sub-estuary to near the Huangmaohai sub-estuary, potentially fueled by nutrients mixed upward from the deep in addition to riverine inputs , Qiu et al 2019. The maximum Chl a concentration was > 40 μg L -1 off the Modaomen sub-estuary, accompanied by an extraordinarily high DO concentration of > 350 μmol kg -1 (Fig.…”
Section: Destruction Of Hypoxia By the Typhoonmentioning
confidence: 95%
“…1c, d) and offshore spreading of the river plume. A stronger bloom was identified in the surface plume, widely spreading from the mouth of the Lingdingyang sub-estuary to near the Huangmaohai sub-estuary, potentially fueled by nutrients mixed upward from the deep in addition to riverine inputs , Qiu et al 2019. The maximum Chl a concentration was > 40 μg L -1 off the Modaomen sub-estuary, accompanied by an extraordinarily high DO concentration of > 350 μmol kg -1 (Fig.…”
Section: Destruction Of Hypoxia By the Typhoonmentioning
confidence: 95%
“…In contrast, in the bottom water, high nutrient concentrations were observed during the pre-typhoon period. The reasons for this may be nitrification caused by a strong thermocline and halocline during the summer [9,23]. The study carried out by Chen et al in the offshore NSCS showed that the ammonia concentration was significantly lower than the nitrate one in the bottom water, where dual nitrate isotopic characterization confirmed that nitrification occurred [23].…”
Section: Nutrient Characterization During the Pre-typhoon Periodmentioning
confidence: 98%
“…In summer, particularly, heavy rainfall resulted in greater discharges from local rivers into nearshore areas. These discharges might have carried more domestic sewage into the coastal seawater, leading to the higher nutrient concentrations observed in that season [4,9,29,30]. Furthermore, fertilizers were applied widely in the agriculture of Guangdong Province in spring and summer [5,23], and could have been carried to the coastal area by the river discharges of the latter season.…”
Section: Nutrient Characterization During the Pre-typhoon Periodmentioning
confidence: 99%
See 2 more Smart Citations